Spillovers and correlations between US and major European stock markets: The role of the euro - Savva, Christos S.; Osborn, Denise R.; Gill, Len (My University, 2009)
This article investigates the impact of the introduction of the euro on the interactions across the New York, London, Frankfurt and Paris stock markets. After controlling for possible returns and volatility spillovers, we focus on the correlations of shocks using the framework of Dynamic Conditional Correlations (DCC). Daily pseudo-closing prices (recorded at 16:00 London time) are used to avoid conflating correlation and spillover effects. Statistical break tests confirm that the introduction of the euro significantly affects the cross-market correlations. Although dynamic correlations of shocks between all market pairs increase, the correlation in the post-euro period is highest between Frankfurt and Paris, indicating increased integration of these markets. Other findings include the presence of spillover effects from foreign markets for both returns and volatilities, with asymmetries in volatilities and conditional correlations such that negative shocks have larger effects than positive ones.
Keywords: Capital flow; Stock market; Volatility spillovers; Contagion; Correlation; Currency market; European Monetary Union; Inflation; Market conditions; Market system; Price dynamics; Spillover effect; Stock market